2021
DOI: 10.33448/rsd-v10i2.12906
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of untreated second canal in the mesiobuccal root of maxillary molars and its association with apical periodontitis: A cone beam computed tomography study

Abstract: This study aimed to evaluate the prevalence of mesiobuccal 2(MB2) canals not located/treated in maxillary molars and correlated their non-treatment with the presence of periradicular lesion. The study was conducted on 180 cone beam computed tomography (CBCT) scans. The 180 examinations added up to 210 teeth analyzed (140 maxillary first molars and 70 maxillary second molars). The presence of non-located/treated MB2 canals and periapical lesions in the mesiobucal(MB) root was identified by observation of the ax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 19 publications
1
4
0
1
Order By: Relevance
“…The agreement analysis in the present study demonstrated a slight concordance of the digital radiography in relation to CBCT, being the superiority of this last one proved by a greater detection of MB2. These findings are supported with results from previous studies comparing the accuracy of this and other methods with CBCT (Machado et al, 2021;Pereira et al, 2021;Ratanajirasut et al, 2018;Torres et al, 2015). Thus, CBCT can be considered a great and reliable option for routine clinical use.…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…The agreement analysis in the present study demonstrated a slight concordance of the digital radiography in relation to CBCT, being the superiority of this last one proved by a greater detection of MB2. These findings are supported with results from previous studies comparing the accuracy of this and other methods with CBCT (Machado et al, 2021;Pereira et al, 2021;Ratanajirasut et al, 2018;Torres et al, 2015). Thus, CBCT can be considered a great and reliable option for routine clinical use.…”
Section: Resultssupporting
confidence: 88%
“…The Figure 1 shows images highlighting the absence or presence of MB2 canal, by using some method of assessment of this study. The variation in the morphology of the root canal system in multiradicular teeth remains challenge in Endodontics (Machado et al, 2021;Ordinola-Zapata et al, 2017;Pereira et al, 2021). With technological advancement the CBCT, DR and visual magnification are becoming a reality in successful endodontic treatment, as they allow considerable advantages in terms of quality, efficiency, and security to clinical and specialist.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations